MAKNA PELEKATAN SIDIK JARI DALAM MINUTA AKTA NOTARIS - Duhita Sresti Abhirama (Trunojoyo Madura University, 2018)
Notary as a general official in carrying out his office always based on the authority, obligations and restrictions set forth in UUJN. One of the obligations of a notary is to attach fingerprints in every minuta deed made. Some time ago, the notary was confused which meant the fingerprints were the thumb or 10 (ten) fingers. The purpose in writing is to examine and analyze the meaning of fingerprint attachment in minuta deed. Research method in writing is normative juridical with statute approach and conceptual approach. The results showed that fingerprint attachment does not affect the authenticity of notary deed. Terms of authentic deeds have been regulated in Article 1868 BW and Article 38 UUJN. The aforementioned obligation aims at protecting the Notary from denial of signature signature and serves as additional proof that the confrontation is right with the Notary. If the responders refuse to attach their fingerprints, the notary must provide a reason for the fingerprint attachment to the cover. Despite the deed without any fingerprints, the deed remains authentic and not degraded to the deed under the hand. Notary if the attachment is not attached, the notary will get sanction from the Supervisory Board.